The Game Of 'What Falls' Through Information Services At Senior High School 1 Kurun, Kuala Kurun - Suriatie, Mimi; Sangalang, Oktamia Karuniaty; Pangestie, Esty Pan; Feronika, Nopi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
A teacher is highly expected for the benefit of effectiveness and efficiency of Guidance and Counseling services in schools. Teachers can also act as mentors for their students. One of the government's policies is to promote guidance and counseling in schools to assist the educational process and the quality of human resources. The purpose of this study